Language demography - Moreno Fernández, Francisco (Routledge Taylor & Francis Group, 2024)
"Language Demography explores the emergence and development of language demography and looks especially for the presentation of the linguistic concepts involved in demography and the demographic concepts involved in sociolinguistics. The first introductory guide of its kind, it is presented in a way that is accessible to non-specialists. The book includes numerous examples of the sources and types of data used in this field, as well as the various factors affecting language demography. Taking a global perspective supported by examples, explanations of how demolinguistic analyses are performed and their main applications in relation to minority and majority languages are given. Language Demography will be of interest to students from a range of disciplinary backgrounds, from linguistics and modern languages to sociology, anthropology, and human geography"--
Includes bibliographical references and index
Keywords: Linguistik; Demographie